2023
DOI: 10.21037/sci-2022-042
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of adeno-associated virus (AAV) gene delivery into human bone marrow stem cells (hBMSCs)

Abstract: Background Efficiently delivering nucleic acid into mammalian cells is essential to overexpress genes for assessing gene functions. Human bone marrow stem cells (hBMSCs) are the most studied tissue-derived stem cells. Adeno-associated viruses (AAVs) have been used to deliver DNA into hBMSCs for various purposes. Current literature reported that transduction efficiencies of up to 65% could be achieved by AAV gene delivery into hBMSCs. Further improvement of efficiency is needed and possible. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…genomic solution at a concentration of 1.0 x 10 12 GC/ mL was mixed with 140 µL of the medium and applied. After overnight incubation, the medium was changed every 2 days and evaluated on day 7 [21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…genomic solution at a concentration of 1.0 x 10 12 GC/ mL was mixed with 140 µL of the medium and applied. After overnight incubation, the medium was changed every 2 days and evaluated on day 7 [21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Blum et al demonstrated that MSCs genetically modified with Ad-BMP2 have a higher osteogenic capacity then cells infected with lentiviral constructs or lipoplexes [ 28 ]. At the same time, adeno-associated viruses have significant limitations for gene therapy of bone regeneration due to their low ability to transduce osteogenic precursors such as bone marrow-derived MSCs [ 29 ] and the high variability in infection efficiency from donor-to-donor [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…AAV has many serotypes and variants and different AAV serotypes exhibit significant differences in the transduction efficiencies and cell and tissue tropism ( Yao et al, 2023 ). Selection of the appropriate AAV serotype is one of the first steps in designing AAV gene delivery ( Wiley et al, 2018 ).…”
Section: Biological Vectorsmentioning
confidence: 99%
“…Although this mutant showed a slightly higher affinity for heparin compared to AAV2, it is observed similar levels of binding of AAV1.9 and AAV2 to hESCs ( Asuri et al, 2012 ). In another study, AAV2 is highly efficient in delivering genes into human bone marrow stem cells (hBMSCs) ( Yao et al, 2023 ). High transduction efficiencies (>80%) can be achieved by adding virus particles to cell cultures at MOI OF 10,000.…”
Section: Biological Vectorsmentioning
confidence: 99%
See 1 more Smart Citation